Bumping and Grinding On the Line: Making Nudity Pay - Ross, Becki L. (Labour / Le Travail, 2000)
This paper invites labour and queer historians and sociologists to reconsider frameworks that have excluded attention to experiences of female workers who, throughout the 20th century, supplied sexual services to (largely) male consumers. Specifically, Vancouver, BC, 1945-1980, acts as a case study for the exploration of postwar erotic entertainment – burlesque, go-go dancing, and striptease. Preliminary archival and ethnographie findings reveal the working conditions and artistic influences of former dancers, the racialized expectations of erotic spectacle, and the queer dimensions of strip culture. Adored and celebrated by fans, stripteasers also laboured under the 'whore stigma' circulated by moral reformers, the popular press, and the police. It is this tension between the reverence and the hostility aroused by erotic dancers that forms a central theme of the paper.